Daughters and Inheritance: Babylonian Boundary Stone 9 and Numbers 27 - Campbell, Nicholas J. (Perichoresis, 2024)
A daughter’s ability to inherit property is treated differently in various ancient Near Eastern cultures. This paper examines the difference between land inheritance by daughters in Israel and Babylon using the text of Numbers 27 and Babylonian Boundary Stone 9. The unique status of land and land allotment in the two societies are explored as well as the implications for the status of daughters. The conclusion from the comparison is that the biblical text excludes daughters because of limited landholdings and the desire to maintain the property inheritance from the initial land allotment event. However, Babylonian Boundary Stone 9 allows daughters to inherit more easily because of fluid landholdings and multiple (royal) land allotment events.